1968
DOI: 10.1001/archpedi.1968.02100020220018
|View full text |Cite
|
Sign up to set email alerts
|

Erythrodermic Psoriasis in Childhood

Abstract: PSORIASIS is a chronic inflammatory skin disorder of unknown etiology and and inconstant course. It is said to occur in 1% to 2% of the white population, but is rare in Negroes.1 The disease is relatively uncommon in the pediatric age range, particularly in children under 3 years of age.2 The diffuse erythrodermic form is extremely rare in young children.3,4The purpose of this report is to present a case of erythrodermic psoriasis in a Negro child whose disease began about 18 months of life. Perlman states tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1968
1968
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Treatment also led to a significant decrease in the Children’s Dermatology Life Quality Index (from 9.0 to 3.8 at week 24) without severe adverse events [most reported adverse events were severe nausea (20%), infections requiring antibiotics (20%) and tiredness (16%)] [ 57 ]. There are also several case reports and small case series demonstrating the benefits of MTX in the treatment of recalcitrant plaque psoriasis, erythrodermic psoriasis, pustular psoriasis and severe palmoplantar psoriasis in children as young as 2 years of age [ 55 , 59 66 ]. Significant clinical improvement was noted after as little as 5 weeks of therapy, and clinical remissions were reported that ranged in duration from 1.5 months to 3 years.…”
Section: Non-biologic Systemic Drugsmentioning
confidence: 99%
“…Treatment also led to a significant decrease in the Children’s Dermatology Life Quality Index (from 9.0 to 3.8 at week 24) without severe adverse events [most reported adverse events were severe nausea (20%), infections requiring antibiotics (20%) and tiredness (16%)] [ 57 ]. There are also several case reports and small case series demonstrating the benefits of MTX in the treatment of recalcitrant plaque psoriasis, erythrodermic psoriasis, pustular psoriasis and severe palmoplantar psoriasis in children as young as 2 years of age [ 55 , 59 66 ]. Significant clinical improvement was noted after as little as 5 weeks of therapy, and clinical remissions were reported that ranged in duration from 1.5 months to 3 years.…”
Section: Non-biologic Systemic Drugsmentioning
confidence: 99%
“…This report illustrates a severe presentation of congenital erythrodermic psoriasis with decreased serum complement level and shows the difficulty of reaching a correct diagnosis when confronted with congenital erythroderma. Congenital psoriasis is rare, and even rarer in the form of erythroderma 1 –3 . The more common forms of congenital psoriasis are localized or guttate 4 –6 .…”
mentioning
confidence: 99%
“…4 Patogenesis psoriasis anak multifaktorial, tetapi belum semua teori dapat dijelaskan secara pasti. Pada psoriasis terjadi akselerasi dari siklus germinativum epidermis yang mengakibatkan proliferasi keratinosit dan vaskularisasi di kulit dengan pemendekan waktu merenovasi epidermis yang diperantarai oleh sel limfosit T. 5,6 Gambaran histopatologik psoriasis pada epidermis tampak parakeratosis, akantosis reguler, hilangnya stratum granulosum, dan elongasi reguler rete ridges dengan penebalan di area basal. Pada dermis sering tampak edema papila dan dilatasi kapiler.…”
Section: Pembahasanunclassified